2000
DOI: 10.1128/aac.44.10.2811-2815.2000
|View full text |Cite
|
Sign up to set email alerts
|

Valganciclovir Results in Improved Oral Absorption of Ganciclovir in Liver Transplant Recipients

Abstract: The pharmacokinetics of an orally administered valine ester of ganciclovir (GCV), valganciclovir (VGC), were studied. These were compared to the pharmacokinetics of oral and intravenous GCV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
238
2
3

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 327 publications
(252 citation statements)
references
References 25 publications
6
238
2
3
Order By: Relevance
“…Valganciclovir, a valine ester of ganciclovir, provides sys temic ganciclovir levels that are comparable to IV ganci clovir [73,76] . Pharmacokinetic studies indicate that a 900 mg dose of valganciclovir achieves a similar daily area under the concentration time curve (AUC24) as an IV dose of 5 mg/kg of ganciclovir [73] .…”
Section: Valganciclovir Prophylaxismentioning
confidence: 99%
“…Valganciclovir, a valine ester of ganciclovir, provides sys temic ganciclovir levels that are comparable to IV ganci clovir [73,76] . Pharmacokinetic studies indicate that a 900 mg dose of valganciclovir achieves a similar daily area under the concentration time curve (AUC24) as an IV dose of 5 mg/kg of ganciclovir [73] .…”
Section: Valganciclovir Prophylaxismentioning
confidence: 99%
“…Valganciclovir, a valine ester of ganciclovir, which results in enhanced absorption, resulting in systemic drug levels that are comparable to IV ganciclovir [68,71] . Pharmacokinetic studies indicate that a 900 mg dose of valganciclovir achieves a similar daily area under the concentration time curve (AUC 24 ) as an IV dose of 5 mg/kg of ganciclovir [68] .…”
Section: Valganciclovir Prophylaxismentioning
confidence: 99%
“…Previous pharmacokinetic studies showed similar drug exposure to ganciclovir after a single oral dose of 900 mg valganciclovir as compared to an intravenous dose of 5 mg/kg ganciclovir. [9][10][11] Recently, oral valganciclovir and intravenous ganciclovir were shown to have similar efficacy in pre-emptive CMV treatment in solid organ transplant recipients. [12][13][14] As a consequence, the prevention of CMV disease in high-risk renal, renal-pancreas and heart transplant patients was added as another indication to the original approval of valganciclovir for the treatment of CMV retinitis in AIDS patients.…”
Section: Introductionmentioning
confidence: 99%